(untitled) (Ukrainian Journal of Ophthalmology, 2026)
Introduction. Existing methods of treatment for bacterial keratitis do not always provide a positive therapeutic effect and do not prevent the occurrence of relapses. The main reason for this is the development of resistance of microorganisms to antibiotics. The use of silver nanoparticles with antimicrobial properties may be promising in the treatment of bacterial keratitis. However, the effect of silver nanoparticles on the structure of the cornea has not been adequately studied. Objective: to study the effect of instillations of a colloidal solution of silver nanoparticles measuring 30 nm on the ultrastructure of the epithelium and stroma of the rabbit’s cornea. Material and Methods. The colloidal solution of silver nanoparticles 30 nm in size was instilled into the conjunctival cavity of rabbits three times a day. Ultrastructural changes in epithelial cells and corneal stroma, changes in connective tissue plates and collagen fibrils of the stroma were evaluated at Days 15 and 30 of the experiment. Results. The effect of silver nanoparticles caused an increase in the number of ribosomes in the superficial cells of the corneal epithelium, hydrophilic changes in membrane organelles, an increase in the number of ribosomes in all cells of the basal layer, and destruction of individual organelles in single cells. In the stroma, the edema of the main substance was observed; the areas of defibration, homogenization or fragmentation of collagen fibril bundles were determined. The dystrophic changes were more severe as the duration of instillations of silver nanoparticles increased. Conclusions. The daily instillations of the colloidal solution of silver nanoparticles measuring 30 nm in the conjunctival cavity in the course of 15 and 30 days caused the dystrophic changes in the superficial and basal cells of the corneal epithelium. In the stroma of the cornea, the dystrophic changes in keratocytes, violation of the architectonics of connective tissue plates, defibration and fragmentation of collagen fibrils were detected.